Аппаратура автоматизации очистных комбайнов - Захаров В. Н. Владимир Николаевич; Кириченко К. И. Константин Иванович; Силаев В. И. Виктор Иванович; Сирченко В. Н. Владимир Николаевич (Москва, Недра, 1986)
Авт. указаны на обоороте тит. л.